1982
DOI: 10.1136/bmj.285.6343.689
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pain relief in labour: survey of 1000 mothers

Abstract: The amount of pain that had been experienced by 1000 women during vaginal delivery of a live child was determined by interview within 48 hours of delivery. Patients had been offered a choice of analgesia, and 536 had received epidural analgesia: pain relief was greatest in this group, just over half having had a painless labour. The duration of pain was also reduced by a third in this group even though patients who had received an epidural block had tended to have longer labour and an incidence of assisted del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…Of the remaining 278 women who answered the questionnaire, 134 (48%) were primiparas and 144 (52%) multiparas. The average age was 29 years (range 18-43) and education 13 years (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Almost all women were married or co-habiting (96%), and 88% were born in Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 278 women who answered the questionnaire, 134 (48%) were primiparas and 144 (52%) multiparas. The average age was 29 years (range 18-43) and education 13 years (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Almost all women were married or co-habiting (96%), and 88% were born in Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other studies, the present study has evidenced an association of this medical practice to women's socioeconomic status. 13 In the US, Hueston et al 9 (1994) also found higher administration of peridural anesthesia in white women who at the same time received more specialist care.…”
Section: Discussionmentioning
confidence: 98%
“…Wuitchik et al (1990) showed that anxiety could persist even after adequate pain relief was achieved. Morgan et al (1977) concluded that, although analgesia was effective for pain relief, it could provoke anxiety and affect the birth experience.…”
Section: Maternal Anxiety and Painmentioning
confidence: 99%